Managing Multi-Center Recruitment in the PLCO Cancer Screening Trial - K. Gohagan, John; Broski, Karen; H. Gren, Lisa; N. Fouad, Mona; Higgins, Darlene; Lappe, Karen; Ogden, Sheryl; Shambaugh, Vicki; F. Pinsky, Paul; O128;™Brien, Barbara; Yurgalevich, Susan; Riley, Tom; et al. (Reviews on Recent Clinical Trials, 2015)
There were significant recruitment challenges specific to the PLCO Cancer Screening Trial. Large numbers of participants were to be randomized from ten catchment areas nationwide within time and budgetary constraints. The eligible population was elderly and had to meet health and behavioral thresholds. Informed consent was required to participate and be randomized to screening for three cancers at periodic clinic visits or to a usual care arm that included no clinical visits. Consenting required special efforts to fully explain the trial and its potential scientific benefit to future patients with potentially no benefits but possible harms to PLCO participants. Participation would include continued follow-up for at least 13 years after randomization. Strong collaborative investments were required by the NCI and screening centers (SCs) to assure timely recruitment and appropriate racial participation. A trial-wide pilot phase tested recruitment and protocol follow through at SCs and produced a vanguard population of 11,406 participants. NCI announced the trial nationally in advance of the pilot and followed with an even more intense collaborative role with SCs for the main phase to facilitate trial-wide efficient and timely recruitment. Special efforts to enhance recruitment in the main phase included centralized and local monitoring of progress, cross-linking SCs to share experiences in problem solving, centralized training, substantial additional funding dedicated to recruitment and retention, including specialized programs for minority recruitment, obtaining national endorsement by the American Cancer Society, launching satellite recruitment and screening centers, including minority focused satellites, and adding a new SC dedicated to minority recruitment.
Keywords: eligibility